(untitled) (LACCEI, 2024)
This article describes an experience in the application of geolocated activities to teach first-year students of an engineering university education program, the fundamentals of object-oriented programming and software modeling, generating a motivating and effective environment for their learning. Object-oriented programming is based on general concepts that are known and applied by human beings in general in their daily lives, but its teaching creates challenges that must be faced, mainly due to its abstract nature. Software modeling is a very useful tool for any professional who develops software and it is best to learn it from the beginning of their university studies. It is shown that a teaching based on the application of geolocated activities to teach the concepts of object-oriented programming and software modeling is motivating and effective for students belonging to the Centennial Generation.